A Critical Analysis and Review of the Sustainable Livelihoods Approach for Rural Development - Lusinga-Machikicho, Susan; Mutanana, Ngonidzashe (Advances in Social Sciences Research Journal, 2022)
The main objective of this paper was to evaluate and analyse the importance of the Sustainable Livelihoods Approach (SLA) and its application to policies and projects for rural development. Literature focusing on the main components of the SLA was reviewed. The paper noted that the SLA is effective in interrogating the livelihoods of the poor and the various mechanisms contained in the approach such as all forms of capital, the vulnerability aspect, livelihood strategies and outcomes as well as the various laws and regulations governing the access and use of resources. It has been observed by leading scholars such as Chambers and Scoones (1992) as an inclusive and top- down approach. The approach has theoretically proven that it assists in understanding the livelihoods of the poor in rural communities. It is recommended that government and their development partners adopt and incorporate the SLA into their policies for sustainable livelihoods and development.